2019
DOI: 10.1002/pssr.201900329
|View full text |Cite
|
Sign up to set email alerts
|

Rhenium Diselenide Anchored on Reduced Graphene Oxide as Anode with Cyclic Stability for Potassium‐Ion Battery

Abstract: An effective route is developed to fabricate ultrathin rhenium diselenide (ReSe2) nanosheets anchored on reduced graphene oxide (rGO) nanoflakes (ReSe2@rGO). When the ReSe2@rGO is used as an anode material in the potassium‐ion batteries (PIBs), the graphene offers a conductive matrix to buffer the volume alteration during repeated K+ insertion/extraction cycles. The stable interfacial connection between ReSe2 and graphene greatly promotes the integration of the active ReSe2 nanosheets, preventing their agglome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 41 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…Intercalation‐conversion materials mainly consist of transition metal compounds, which mainly include oxides, 104‐106 sulfates, 107‐109 selenides, 110,111 and tellurides 112,113 with the reaction of M a X b + (b.n)K ↔ K bn M a X b ↔ a M + b K n X for PIBs. M denotes the transition metal like Fe, Co, Ni, Mo, Re, and so on, X denotes the anion (O, S, Se, Te, etc .…”
Section: Carbon‐based Composite Materials For Potassium‐ion Batteriesmentioning
confidence: 99%
“…Intercalation‐conversion materials mainly consist of transition metal compounds, which mainly include oxides, 104‐106 sulfates, 107‐109 selenides, 110,111 and tellurides 112,113 with the reaction of M a X b + (b.n)K ↔ K bn M a X b ↔ a M + b K n X for PIBs. M denotes the transition metal like Fe, Co, Ni, Mo, Re, and so on, X denotes the anion (O, S, Se, Te, etc .…”
Section: Carbon‐based Composite Materials For Potassium‐ion Batteriesmentioning
confidence: 99%
“…In addition, PIBs possess several significant advantages, such as the more negative standard redox potential of K + /K (− 2.93 V vs. standard hydrogen electrode (E 0 )) compared to that of Na + /Na (− 2.71 V vs. E 0 ), the fast ionic conductivity of K + in electrolyte, and the alternative use of Al foil to Cu foil [12,[19][20][21][22]. These characteristics provide promising opportunities for PIBs to be developed as low-cost batteries with good rate performance and high energy density [23][24][25][26][27]. At the current stage, it is still a big challenge to select suitable electrode materials that can accommodate huge volume variations during the cycles [28].…”
Section: Introductionmentioning
confidence: 99%
“…possess nature abundant and high theoretical capacity, which have been treated as promising anode materials for the next-generation PIBs. However, the partial dissolution of polysulfide intermediates and large volumetric change during the potassium insertion/extraction will result in fast capacity fading, which seriously limits their practical applications, and one effective strategy to solve the above problems is to construct the carbon materials with the nanocomposites of transition metal sulfide [25,29]. Therefore, Xia et al [30] reported a few layers SnS 2 nanosheets supported on reduced graphene oxide Available online at http://link.sprin ger.com/journ al/40195 .…”
Section: Introductionmentioning
confidence: 99%
“…Other selenides, like GeSe [215][216][217], TiSe2 [218], ReSe2 [219], CoSex [220][221][222], ZnSe [223,224], VSe2 [225], Ta4NiSe5 [226], and NbSe2 [227], were also prepared and employed as the anodes of PIBs, and all these PIBs show excellent electrochemical performance for K + storage. For instance, Ma et al have reported the fabrication of ReSe2 nanosheets anchored on rGO nanoflakes (Fig.…”
Section: Metal Selenidesmentioning
confidence: 99%
“…For instance, Ma et al have reported the fabrication of ReSe2 nanosheets anchored on rGO nanoflakes (Fig. 11(c)) [219]. The layered structure of ReSe2 can facilitate the interaction of K + and shorten the ion diffusion path, while rGO sheets offer the conductive matrix to buffer the volume changes during cycles.…”
Section: Metal Selenidesmentioning
confidence: 99%